2013
DOI: 10.1111/j.1467-8268.2013.12032.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Information and Communication Technology Use and Firm Performance in Developing Countries: A Case Study of Electrical and Electronic Goods Manufacturing SMEs in Tunisia

Abstract: From the second half of the 1990s, increased investment in Information and Communication Technologies (ICTs) has led to an acceleration of productivity growth and performance in many developed and newly industrialized countries. However, less is known about the current situation of firms in developing countries. This article addresses this issue by examining the relationship between ICT use and the performance of Tunisian SMEs operating in the electrical and electronic industry based on net profit margin. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
(45 reference statements)
2
9
0
6
Order By: Relevance
“…Based on a study in Uganda, the majority of respondents strongly agree that ICTs contribute to increased savings (52%), increased efficiency (81%), improved service delivery (61%), decreased transaction costs (47%), and improved market performance (38%) to the organization that invests in ICT (Ssewanyana & Busler, ). The literature also pointed out the need to look at the usability of ICT application by the decision makers to understand the actual use of IT in improving performance (Basant, Commander, Harrison, & Menezes‐Filho, ; Bloom, Sadun, & van Reenen, ; Piget & Kossaï, ; Ratten, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on a study in Uganda, the majority of respondents strongly agree that ICTs contribute to increased savings (52%), increased efficiency (81%), improved service delivery (61%), decreased transaction costs (47%), and improved market performance (38%) to the organization that invests in ICT (Ssewanyana & Busler, ). The literature also pointed out the need to look at the usability of ICT application by the decision makers to understand the actual use of IT in improving performance (Basant, Commander, Harrison, & Menezes‐Filho, ; Bloom, Sadun, & van Reenen, ; Piget & Kossaï, ; Ratten, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…11; firms in forms of increased employee wages/salaries and other benefits. On the other hand, studies have shown that ICT infrastructures have not only improved operational efficiency of firms but have also given the firms strategic competitive advantage (Chae, Koh, & Prybutok, 2014;Piget & Kossai, 2013;Shan & Jolly, 2013). However the positive performance effects of ICT are no longer visible especially in the last decade as the ICT capabilities become increasingly commoditised and therefore no longer give a firm a competitive edge.…”
Section: Other Determinants Of Firm Performancementioning
confidence: 99%
“…In finance such factors as working capital management, taxes & theft, ownership structure and portfolio concentration and the their relationships with firm profitability have also been explored (Aktas, Croci, & Petmezas, 2015;Ekholm & Maury, 2014;Huang & Boateng, 2013;Mironov, 2013). Finally the effects of technology-related factors, operational efficiency and business ethics on firm profitability have equally been the subject of studies on firm performance literature (Baik, Chae, Choi, & Farber, 2013;Eisenbeiss, Knippenberg, & Fahrbach, 2015;Chae, Koh, & Prybutok, 2014;Piget & Kossai, 2013 ;Shan & Jolly, 2013). This section provides research background to the study on the relative effects of industry and business-specific factors on firm performance.…”
Section: Introductionmentioning
confidence: 99%
“…Las TIC, han provocado una mayor automatización de los procesos productivos, de servicios y comerciales, incidiendo en la disminución de los empleados (Ashford & Hall, 2011;Torres-Coronas, 2012). Estudios recientes en Pymes del sector manufactura señalan que mediante el establecimiento de las TIC y la alineación de una estrategia basada en innovación tecnológica, se logran altos niveles de competitividad, se elevan las ventas y se mejoran las habilidades de los empleados Piget & Kossaï, 2013). De lo anterior se hace el siguiente planteamiento: El tamaño muestral fue determinado para lograr que el margen de error máximo para la estimación de una proporción (frecuencia relativa de respuesta en un ítem específico de una cuestión) fuese inferior a 0.03 puntos con un nivel de confianza del 95%.…”
Section: La Gestión Del Conocimiento Y El Crecimiento Empresarialunclassified
“…Este estudio analiza el incremento de las ventas y de los empleados como componentes del crecimiento empresarial. Además existe una limitada evidencia empírica enfocada en la Pyme, en esta área del conocimiento(Chawan & Vasudevan, 2013;Piget & Kossaï, 2013). Capítulo 2: Las TIC y la gestión del conocimiento, elementos determinantes para el crecimiento de la Pyme…”
unclassified